2002
DOI: 10.1074/jbc.m200604200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of the PsbS Subunit of Photosystem II Either Purified from Chloroplast or Recombinant

Abstract: The biochemical properties of PsbS protein, a nuclearencoded Photosystem II subunit involved in the high energy quenching of chlorophyll fluorescence, have been studied using preparations purified from chloroplasts or obtained by overexpression in bacteria. Despite the homology with chlorophyll a/b/xanthophyllbinding proteins of the Lhc family, native PsbS protein does not show any detectable ability to bind chlorophylls or carotenoids in conditions in which Lhc proteins maintain full pigment binding. The reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 56 publications
4
121
0
8
Order By: Relevance
“…In higher plants the 'special' polypeptide which undergoes protonation is PsbS . The function of PsbS is essentially to sense the lumen pH, that is linked to several H + -binding amino acid residues present on the luminal loops of this protein (Dominici et al 2002;Li et al 2002). In green microalgae (Peers, G and Niyogi, KK, personal communication, 2008) and diatoms (Zhu and Green 2008), the Li-818 proteins which are up-regulated under high light, could play a similar role as PsbS in qE.…”
Section: Effect Of Light Stress On Fluorescence Signatures and Their mentioning
confidence: 99%
“…In higher plants the 'special' polypeptide which undergoes protonation is PsbS . The function of PsbS is essentially to sense the lumen pH, that is linked to several H + -binding amino acid residues present on the luminal loops of this protein (Dominici et al 2002;Li et al 2002). In green microalgae (Peers, G and Niyogi, KK, personal communication, 2008) and diatoms (Zhu and Green 2008), the Li-818 proteins which are up-regulated under high light, could play a similar role as PsbS in qE.…”
Section: Effect Of Light Stress On Fluorescence Signatures and Their mentioning
confidence: 99%
“…The second type of quenching, known as qE, is pH dependent and requires protonation of lumenal exposed acidic residues in the PsbS subunit (Li et al, 2002b), which has DCCD binding sites (Dominici et al, 2002). Both types of quenching have been proposed to imply conformational changes in LHC proteins (Gilmore and Ball, 2000;Horton et al, 2000).…”
Section: Relation Between Ph-independent and Qe Quenching Typesmentioning
confidence: 99%
“…The interchange of these carotenoids via the intermediate antheraxanthin (Anthera), reversible in the dark by zeaxanthin epoxidase, is called xanthophyll cycle. Low lumenal pH also results in protonation of specific light-harvesting complexes (LHCs) (Dominici et al, 2002;Li et al, 2002a;Li et al, 2002b;Pesaresi et al, 1997;Walters et al, 1996), which, synergistically with zeaxanthin binding, leads to a conformational change necessary for NPQ (Moya et al, 2001). The PSII subunit S (PsbS) was found to be essential for NPQ (Li et al, 2000) and may trigger the quenching in a series of steps involving protonation and, possibly, zeaxanthin binding (Li et al, 2002b;Holt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In Chlamydomonas, elimination of one of the major LHCIItype complexes had a significant effect on qE, although in plants the lack of Lhcb1 and Lhcb2 only reduced qE capacity by about 20% (23). Mutants lacking the Lhc-related protein PsbS almost completely lack qE (24), although the exact role of PsbS is unclear, partially due to uncertainties of its pigment binding capabilities (25)(26)(27)(28)(29)(30). It has been suggested that PsbS may be a regulatory subunit in qE rather than being the site of quenching per se (31), providing binding sites for protons (32) and zeaxanthin (33).…”
mentioning
confidence: 99%